Magnetic Susceptibility Properties of Loess From the Willendorf Archaeological Site: Implications for the Syn/Post-Depositional Interpretation of Magnetic Fabric - Zeeden, Christian; Hambach, Ulrich (Frontiers in Earth Science, 2021)
At the Willendorf site Upper Paleolithic archeological layers associated to early Aurignacian cultures were found. The environmental conditions of the associated society, potentially co-existing with Neanderthal groups, is still not fully understood. Here, we report on environmental magnetic analyses including anisotropy of the magnetic susceptibility (AMS) carried out on loessic aeolian sediments at the Willendorf site. Data on lineation, foliation and the degree of anisotropy were used to assess depositional and post-depositional magnetic fabric properties and to deduce site-specific environmental processes. Overall, the loess is of aeolian origin and shows magnetic enhancement and magnetic fabric properties similar to those of other European loess geoarchives, but the magnetic mineralogy differs from many ‘dry’ loess sites, insofar as it shows a higher susceptibility during heating. We infer an enhanced neoformation of magnetite during heating due to the presence of organic matter. While at face value the AMS properties are indicative of pure aeolian loess consistent with previous studies, imbrication suggests post-depositional slope movement toward the Danube, which obscures inferences on palaeo-wind direction. It is well possible that these post-depositional magnetic fabric alterations occur at other localities with similar geomorphological settings.